Sociology in Our Times: The Essentials, 12th Edition - Diana Kendall (Cengage Learning, 2020)
Kendall's SOCIOLOGY IN OUR TIMES: THE ESSENTIALS, 12th edition, introduces you to the study of sociology through real-life stories, told by the people who have lived them, as well as timely topics such as the relationship between suicide, bullying and social media. The author humanizes sociology, showing you how it is at work in society and can be applied to everyday life and the pressing social issues we face. You'll learn how you can make a difference in your community -- and the world. You'll also examine issues making headlines, such as the war on gun control and policies to help prevent military suicides. Photos and videos complement the text's main themes of diversity, the application of sociology to everyday life, global comparisons, media and social change, particularly as it relates to social media and other forms of technology that are spurring new ways of living and interacting. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.